The Effectiveness of Using Visual Aids in Teaching English Vocabulary to Vietnamese Young Learners: An Experimental Study - Nguyen, Thanh Thai; Pham, Hong Thi Thanh (English Education and Applied Linguistics Journal (EEAL Journal), 2024)
Vocabulary is a crucial component of learning English. Among the various methods employed by teachers, using visuals is one of the most common approaches. But how effective is it? This study aims to evaluate the effectiveness of using visuals in teaching vocabulary to Vietnamese young learners and to examine potential differences in learning outcomes between male and female students. The research was conducted with the participation of 30 first-grade students aged 5 to 6, all of whom were beginner-level English learners. An experimental research design was implemented, with participants divided into two groups: a control group and an experimental group, each comprising 15 students. The experimental group was taught English vocabulary using visuals, while the control group received instruction through traditional teaching methods without additional teaching aids. Data were collected through three assessments: a pre-test, a midterm test, and a post-test. The results demonstrated that visuals are an effective tool for teaching English vocabulary to first-grade students. Additionally, the post-test revealed a significant difference in vocabulary acquisition between male and female students, with females outperforming their male counterparts when learning with visuals. In conclusion, this study highlights the effectiveness of incorporating visuals into vocabulary teaching and recommends their integration to improve learning outcomes. It also suggests tailoring teaching strategies to optimize vocabulary acquisition for both genders.